2008
DOI: 10.1007/s11745-008-3224-z
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Chain Omega‐3 Polyunsaturated Fatty Acids in the Blood of Children and Adolescents with Juvenile Bipolar Disorder

Abstract: Reduced long-chain omega-3 polyunsaturated fatty acids (LCn-3PUFA), including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have been reported in adult patients suffering from depression and bipolar disorder (BD). LCn-3PUFA status has not previously been examined in children and adolescents with BD compared with healthy controls. Fifteen children and adolescents (9-18 years, M ± SD = 14.4 ± 3.48) diagnosed with juvenile bipolar disorder (JBD) and fifteen healthy age and sex-matched controls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 56 publications
(63 reference statements)
11
54
0
Order By: Relevance
“…204,205 A small study compared youth with versus without BD and found large between-group differences in red blood cell membrane concentrations of omega-3 levels; however, these were not significant after controlling for dietary intake. 206 However, greater docosahexaenoic acid levels were associated with significantly lower depressive symptoms in the BD group. The Ryukyus Child Health Study (n=3067 boys and 3450 girls, 12-15 years old) examined fish intake and omega-3 levels in relation to depressive symptoms.…”
Section: Nutritionmentioning
confidence: 91%
“…204,205 A small study compared youth with versus without BD and found large between-group differences in red blood cell membrane concentrations of omega-3 levels; however, these were not significant after controlling for dietary intake. 206 However, greater docosahexaenoic acid levels were associated with significantly lower depressive symptoms in the BD group. The Ryukyus Child Health Study (n=3067 boys and 3450 girls, 12-15 years old) examined fish intake and omega-3 levels in relation to depressive symptoms.…”
Section: Nutritionmentioning
confidence: 91%
“…Several participants received other medication in addition to a primary mood-stabilizer, with the most common being risperidone, dexamphetamine and selective serotonin re-uptake inhibitors. Details of inclusion and exclusion criteria have been described previously (Clayton et al, 2008). Participants had not taken LCn-3PUFA supplements within the previous 12 weeks and were not receiving any medications that affected lipid metabolism or blood coagulation.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting blood samples were collected at each assessment and red blood cells (RBCs) were separated from plasma for analysis of fatty acids using gas chromatography. Details of the assessment of mood, behaviour and RBC fatty acids have been described previously (Clayton et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[66][67][68] Clayton et al found no differences in omega-3 fatty acid concentrations in pediatric bipolar disorder when controlling for the intake of omega-3 fatty acids. 69 Rather, the authors suggest that the high cost of fresh fish and low socioeconomic status often associated with bipolar disorder may account for the lower concentrations of omega-3 fatty.…”
Section: Bipolar Disordermentioning
confidence: 99%